Design improvement of the assembility and disassembility of integrated table, rack and wardrobe (TRW) - Nur Farhana, Mustaffa (2008)
In UMP, the student’s room is cramped with individual product such as study table and wardrobe that causing the limited living space. In order to overcome this, the table, rack and wardrobe (TRW) are proposed to be one unit from three separate units. This paper is aim to proposed a framework of the integrated design. The design concept is aim to apply by adopting the principle of Design for Assembly (DFA) and Design for Disassembly (DFD) concept. The product design properties such as mechanical strength and stress will be analyzed by using the Finite Element Method (FEM). The Pugh Method then is used and it is aim to select the best alternative based on the DFA, DFD and FEM criteria. Afterwards, the fabricating process is done by using punching and bending machine. The consequences of applying all the analysis mentioned to the product are in order to create a better quality and reliability of the product and also improving customer satisfaction.